Kinerja Aparat Dalam Memberikan Pelayanan Administrasi (Studi Pada Kantor Kecamatan Tongauna Kabupaten Konawe) - Yuliana Musin (Jayapangus Press, 2018)
Improving the performance of the apparatus is not only pursued through decisions, but through the enhancement of the capacity of the apparatus in providing various materials on the management of administrative services through structural training at various levels. the performance of apparatus in administrative services is not enough to be done only by using indicators inherent in the recipients of services such as the satisfaction of the service users, but in line with the community's need for quality service from the government, then as a public servant who won the trust of the community, must always refer to the satisfaction of the community which is the main purpose in service delivery and continuously make efforts to improve the performance apparatus, thus the authors are interested in conducting research titled